Investigation of Current Circulation and Bed Sediment Distribution in Segara Anakan Lagoon, Cilacap Regency - Santosa, Dimas Puji; Santoso, Purwanto Bekti; Sugasta, Hervian Handika; Saputra, Doddy Cahyadi; Adibah, Fairuz (Fakultas Teknik Universitas Tanjungpura, 2025)
Segara Anakan is a semi-enclosed lagoon that serves as a transitional zone between fluvial and marine environments, characterized by complex, dynamic morphological features. The hydrodynamic conditions in this area strongly influence sediment transport and deposition, which, in turn, affect the morphological evolution of the lagoon over time. This study aims to analyze current patterns and bottom sediment distribution in Segara Anakan and to identify the relationship between current dynamics and sediment characteristics. The data used include primary data from bottom sediment sampling at 21 observation stations and secondary data on bathymetry, tides, and river discharge. Current modeling was conducted using the Surface-water Modeling System (SMS) with the RMA2 module, while sediment analysis was conducted using a grain-size test by the sieve method. The modeling results show that the maximum current velocity reaches 0.907 m/s, with flow directions varying according to the lagoon’s morphology. Sediment analysis results indicate that sand is the dominant fraction at 13 stations, while mixed sediments are found in the central part of the lagoon. These findings suggest that tidal current strength plays a significant role in controlling sediment transport and deposition patterns within the Segara Anakan lagoon.